2019
DOI: 10.1111/desc.12888
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to special issue on global child development studies

Abstract: As global child development research is taking off, this special issue provides a collection of recent research characterizing child development across the globe, validating behavioral and neuroimaging tools across diverse geographical setting and cultures, exploring relationships between risk and protective factors and diverse child outcomes, and testing novel avenues of innovative intervention. In particular, three prominent themes that emerge from this special issue are (a) research linking biology and beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Emerging evidence from longitudinal research suggests that socioeconomic disparities in child development emerge sometime during the first two years of children’s life. For example, using data from Bangladesh we have previously shown a pattern whereby children perform as expected with regards to developmental milestones at 6 months, but have dropped significantly at 27 months ( Jensen et al, 2019b ). We have also shown that poverty predicts child outcomes via exposure to risks such as poor growth, inflammation, and playful parenting from 27 months onwards, while only playful parenting showed an association with milestone related to language at 6 months ( Jensen et al, 2019c ).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Emerging evidence from longitudinal research suggests that socioeconomic disparities in child development emerge sometime during the first two years of children’s life. For example, using data from Bangladesh we have previously shown a pattern whereby children perform as expected with regards to developmental milestones at 6 months, but have dropped significantly at 27 months ( Jensen et al, 2019b ). We have also shown that poverty predicts child outcomes via exposure to risks such as poor growth, inflammation, and playful parenting from 27 months onwards, while only playful parenting showed an association with milestone related to language at 6 months ( Jensen et al, 2019c ).…”
Section: Introductionmentioning
confidence: 85%
“…Environmental influences on child development are well-known and behavioral studies from throughout the world show that children living in impoverished circumstances tend to reach developmental milestones later than children living in wealthier families. Indeed, a large body of literature from both high and low-income countries has shown that children in poor households perform less well on measures of cognitive functions and language compared with wealthier peers ( Jensen et al, 2019b , c ; Johnson et al, 2016 ; Rubio-Codina and Grantham-McGregor, 2019 ). Emerging evidence from longitudinal research suggests that socioeconomic disparities in child development emerge sometime during the first two years of children’s life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors play a role in supporting children to thrive. Child development is influenced and affected by a complex interplay of environmental and biological elements, including genetic, educational, socio-cultural, and living environment factors (Jensen et al 2019). It is primarily in the nexus between children and their environments that WASH plays an important role.…”
Section: Why Is Child Development Important and What Are The Links With Wash?mentioning
confidence: 99%
“…Panel studies in developing countries typically employ face-to-face data collection (ie, traditional survey instruments), which happens at a low frequency [12,13]. The Demographic and Health Survey, for instance, is updated only every 3 to 5 years.…”
Section: Introductionmentioning
confidence: 99%